PENGARUH DIGITAL MARKETING TERHADAP PERILAKU KONSUMEN DALAM MELAKUKAN PEMBELIAN PRODUK PERTANIAN SECARA ONLINE DI KOTA KENDARI - Taufiq, Dimas Muhammad; Surni; Weka Gusmiarty Abdullah (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2026)
This study aims to analyze the influence of digital marketing on consumer behavior in purchasing agricultural products online in Kendari City. The method used is a quantitative approach with data analysis techniques employing Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The study involved 70 respondents who are active consumers of online agricultural product purchases in Kendari. The results show that digital marketing does not have a significant direct effect on consumer behavior. However, the study also reveals that digital marketing has an indirect influence on consumer behavior through the mediation of the marketing mix. These findings indicate that the effective implementation of digital marketing strategies can enhance the quality of the marketing mix, which in turn affects consumer purchasing decisions. The implications of this research provide insights for business actors, particularly in the agribusiness sector, to optimize the use of digital marketing in shaping consumer loyalty and improving business competitiveness. This study also serves as a reference for policymakers and future researchers in the field of digital marketing for agricultural products. Keywords: Digital Marketing, Consumer Behavior, Agricultural Products, Marketing Mix